Proximate Composition and Mineral Content of Edible Cuttlefish (Sepiella Inermis), Squid (Uroteuthis Duvauceli) and Octopus (Cistopus Taiwanicus) of Bangladesh (Bioresearch Communications, 2023)
Cephalopods are valuable in fisheries and are consumed as seafood in various cuisines around the world. A study was conducted to know the proximate compositions (protein, ash, fat, carbohydrate and moisture) and minerals (calcium, phosphorus and iron) of cephalopods (octopuses, squids, and cuttlefishes) of Bangladesh. Three species, cuttlefish (Sepiella inermis), squid (Uroteuthis duvauceli) and octopus (Cistopus taiwanicus) were selected on the basis of their availability. The average protein was estimated 16.14%, 15.04%, and 14.68% for Cuttlefish, Squid, and Octopus, respectively whereas the amount of carbohydrate was 0.59%, 0.71%, and 0.53% for the three species. The ANOVA test of the findings of the proximate components showed no significant differences among the three groups (p < 0.05). All the three cephalopods have shown quite the same amount of protein (16.14%, 15.04%, 14.68%) as in commonly consumed fish (rui, catla) and shrimp. The findings suggest that these organisms serve as outstanding sources of protein while containing minimal amounts of fat. The lower amount of fat of cephalopods also proves them leaner than other groups in the comparison. Thus, cephalopods can be a promising source of animal protein in Bangladesh. Both the octopus and cuttlefish showed a good amount of calcium and phosphorus, while the squid proved to be an ideal source of iron. This study proposes to investigate the potential of other cephalopods in the human diet further by undertaking a more thorough analysis that includes all necessary micro and macronutrients.Bioresearch Commu. 10(1): 1420-1423, 2024 (January)